Potent Inhibitors of Organic Anion Transporters 1 and 3 From Natural Compounds and Their Protective Effect on Aristolochic Acid Nephropathy. (3rd May 2020) - Li, Caiyu; Wang, Xue; Bi, Yajuan; Yu, Heshui; Wei, Jing; Zhang, Yi; Han, Lifeng; Zhang, Youcai
Abstract: Organic anion transporters 1 and 3 (OAT1 and OAT3) play a critical role in renal drug-drug interactions and are involved in the nephrotoxicity of many anionic xenobiotics. To date, relatively little is known about the interaction of natural compounds with OAT1 and OAT3. Of the 270 natural compounds screened in the present study, 21 compounds inhibited OAT1 and 45 compounds inhibited OAT3. Further concentration-dependent studies identified 7 OAT1 inhibitors and 10 OAT3 inhibitors with IC50 values of <10 μM, and most of them were flavonoids, the most commonly ingested polyphenolic compounds in the diet and herbal products. Computational modeling of OAT1 and OAT3 revealed the important residues for the recognition of inhibitors. The two strong OAT inhibitors, namely wedelolactone and wogonin, were evaluated for their in vivo interactions with the OAT substrate aristolochic acid I (AAI), a natural compound causing aristolochic acid-induced nephropathy (AAN) in many species. The cytotoxicity of AAI increased in two OAT-overexpressing cell lines, with more cytotoxicity in OAT1-overexpressing cells, suggesting a more important role of OAT1 than OAT3 in AAN. Both wedelolactone and wogonin markedly increased serum AAI concentrations in AAI-treated rats and ameliorated kidney injuries in AAI-treated mice. To conclude, the present findings are of significant value in understanding natural compound-drug interactions and provide a natural source for developing treatments for AAN.